The relationship between working capital efficiency and profitability of consumer product companies in Malaysia / Noor Adzlin Othman - Othman, Noor Adzlin (Faculty of Business Management, 2014)
The purpose of this research is an attempt to determine the relationship between working capital efficiency and profitability of consumer product companies in Malaysia. This research will use Return On Equity (ROE) the main indicator. This research includes independent variables which are debt ratio, average collection period, inventories turnover and current ratio. There are three purposes of the studies which are exploratory, descriptive and causal. In this research, the dependent variable and independent variables are related to each other which are cause and effect, which means that this study is a causal research. The purpose of this study is to analyze and explore the relationship between working capital efficiency and profitability whether the result is positive or negative relationship. In addition, this research engage with hypothesis testing which it explains the nature of relationships that can be established between independent variables that debt ratio, average collection period, inventories turnover and current ratio. Data are retrieved from the utilizing journals, internet and Bursa Malaysia for the annually period of 2009-2013. Multiple regressions are applied to as to find the result for this research. By using the Multiple Linear Regression method, the researcher found 5% significant negative relationship of debt ratio towards the return on equity. Meanwhile, with regards to other independent variables which are average collection period, inventory turnover and current ratio it failed to reject null hypothesis at 5% level of significance toward return on equity. The four selected independent variables of capital structure for only small percentage explanation of the dependent variable. Next is the difficulty on using the short period of data which is only provides five (5) years and only 8 listed companies in Bursa Malaysia are using for the sources.